CONTRIBUTION OF SIPENALI PROGRAM IN CHARACTER STRENGTHENING AT SDN BEGAWAT 01, KABUPATEN TEGAL - Rega Sukmawati; Basukiyatno, Basukiyatno; Suriswo, Suriswo (PIONIR: JURNAL PENDIDIKAN, 2026)
Bullying in elementary schools is a manifestation of a serious character crisis, marked by the weakening of core values such as empathy and responsibility. This qualitative research aims to deeply analyze the contribution of the Sipenali Program (System for Bullying Prevention and Management Actions) as a holistic intervention model in the effort to strengthen student character to prevent and manage bullying at SDN Begawat 01. The study's focus is to investigate the extent to which this program successfully cultivates four fundamental characters: empathy, responsibility, courage, and mutual respect. Using an instrumental case study approach with data triangulation techniques (interviews, observation, and documentation) involving the school principal, teachers, students, and parents, the findings show that the implementation of Sipenali successfully and significantly fostered a positive character foundation. The program’s contribution is realized through four systematic components: socialization, a reporting application, coaching sessions, and an Anti-Bullying Week. Specifically, the program succeeded in significantly cultivating empathy, courage, responsibility, and mutual respect among students, establishing a new social norm of positive interaction. This success is underpinned by the strong commitment of school leadership and the active participation of the entire community. Despite facing challenges in the form of negative influences from digital media and the need for intensive collaboration with parents, the Sipenali Program proves to be a fundamental and effective solution in shaping a safe and positive school environment built on character. This research recommends Sipenali as a replicable model for sustainable character strengthening in elementary schools. Keywords: Sipenali Program, Character Strengthening, Bullying, Empathy, Responsibility, Elementary School